Seagrass Meadows as Critical Ecosystems: An Integrated Approach to Conservation Area in Saleh Bay, West Nusa Tenggara - Wiwid Andriyani Lestariningsih; Mahardika Rizqi Himawan; Ibadur Rahman; Putu Satya Pratama Atmaja; Muhammad Hafidz Ibnu Khaldun; Lora Santika; Mahbub Murtiyoso; Soraya Gigentika; Hernawati Hernawati; Cahya Himawan; Rendy Vidya Wibisono (Ilmu Kelautan)
Seagrass beds are crucial for marine ecosystems, providing habitats and food sources for diverse species while naturally protecting coastlines from erosion. These ecosystems play a pivotal role in stabilizing sediments, filtering pollutants, and acting as carbon sinks, which helps mitigate the effects of climate change. Their significance extends to supporting ecotourism and providing essential services to coastal communities, thereby promoting environmental conservation awareness. Saleh Bay, designated as a marine nature reserve, exhibits rich marine biodiversity across its five distinct zones: core, utilization, sustainable fisheries, non-conservation, and other zones. This study aimed a comprehensive understanding of the pivotal role played by seagrass beds in Saleh Bay's integrated ecosystem in West Nusa Tenggara. The density and percentage cover were count from three linear transects and placed perpendicularly to the coastline. Correspondence Analysis (CA) was applied to represents which species most strongly associated with specific zones. Meanwhile, Cluster Analysis was used to grouping specific zones based on the ecological characteristics. A total of eight seagrass species were identified, which dominated by Enhalus acoroides (42.15%) and closely related to Sustainable Fisheries and Utilization zones. Furthermore, the Cluster Analysis indicates that the Utilization and Sustainable Fisheries zones exhibit the highest degree of similarity (90%) based on their density characteristics. This research underscores the broader understanding of seagrass ecosystems. The high similarity between the Utilization and Sustainable Fisheries zones suggests that these areas play complementary roles in supporting the health of seagrass ecosystems. Management plans should integrate these findings to optimize resource use while ensuring ecological sustainability.